(untitled) (Damascus University Journal of agriculture sciences, 2025)
This research was carried out in a private olive farm located in the village of Tal Aswad (15 km northeast of the city of Al-Hasakah), during the agricultural season 2020-2021 and 2021-2022, on fruitful olive trees (Qaisi variety), 22 years old, reared on one trunk using the low sepals method and a distance Planting (7 x 7 m) irrigated by drip in order to study the effect of three fertilization treatments: F0: control treatment without fertilization, F1: fertilization with NPK at a rate of (2.5 kg tree Urea-1 + 1.5 kg Superphosphate. tree-1 + 1 kg Sulfate Potassium Tree-1; F2: Foliar spraying with elements (N, Ca, B) at the rate of (2g Urea liter-1 water + 2g calcium chloride liter-1 water + 1g boron liter-1 water, and three levels of irrigation Supplementary: (I0: control treatment without irrigation, I1: 2irrigation, I2: 4 irrigation) on the growth and productivity of olives under irrigated farming conditions in Al-Hasakah Governorate (the third stabilization zone).The results showed that there were significant differences between the treatments and their interactions in the studied traits. For fertilization treatments, treatment F2: foliar spray (N, Ca, B) excelled in fruit diameter index (0.95 cm), while treatment F1: ground fertilization (NPK) recorded the significantly higher values for each of: parcel length, number of vegetative parcels formed on the tree, number of panicles, fruit weight and tree yield (29.59 cm, 22.22 parcels. Tree-1, 25.29 clusters. Parcel-1, 4.36 g, 28.70 kg. tree-1 respectively). As for the supplementary irrigation treatments, the treatment (I2: 4 irrigation) excelled in each of: parcel length, fruit diameter, number of vegetative parcels formed on the tree, number of flower clusters, fruit weight and tree productivity (27.25 cm, 0.94 cm, 19.11 parcels. Tree- 1, 22.36 clusters.parcel-1, 3.84 g, 25.62 kg. tree-1, respectively). As for the interaction of the studied treatments, the results showed the superiority of the interaction of the F1 fertilization treatment: ground fertilization (NPK) with the supplemental irrigation treatment (I2: 4 irrigation) in each of: parcel length, fruit diameter, number of vegetative parcels formed on the tree, number of flower clusters, Fruit weight and tree yield (33.44 cm, 0.95 cm, 25.11 parcels. tree-1, 26.33 bunches. parcel-1, 4.53 g, 30.33 kg. tree-1 respectively).